Real options and human capital investment - Bas Jacobs (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper extends the standard human capital model with real options. Real options influence investment behavior when risky investments in human capital are irreversible and individuals can affect the timing of the investment. Option values make individuals more reluctant to invest in human capital and, as a result, required returns on the investment increase. Real options may help to explain a larger human capital premium for higher education, smaller responsiveness of higher education investments to financial incentives, and larger sensitivity of higher education to low-return outcomes and human capital risks. Higher tax rates (or lower subsidies) depress human capital investments, but to a lesser extent than in the standard human capital model. A flat income tax remains neutral if education expenditures are fully deductible.
Keywords: G1; H2; I2; J2; 330; Bildungsinvestition; Realoption; Bildungsertrag; Einkommensteuer; Bildungsfinanzierung; Steuerbegünstigung; Theorie